A Dissociation Between Recognition and Hedonic Value in Caloric and Non-caloric Carbonated Soft Drinks - Delogu, Franco; Huddas, Claire; Steven, Katelyn; Hachem, Souheila; Lodhia, Luv; Fernandez, Ryan; Logerstedt, Macee (Frontiers in Psychology, 2016)
Consumption of sugar-sweetened beverages (SSBs) is considered to be a contributor to diabetes and the epidemic of obesity in many countries. The popularity of non-caloric carbonated soft drinks as an alternative to SSBs may be a factor in reducing the health risks associated with SSBs consumption. This study focuses on the perceptual discrimination of SSBs from artificially sweetened beverages (ASBs). 55 college students rated 14 commercially available carbonated soft drinks in terms of sweetness and likeability. They were also asked to recognize if the drinks contained sugar or a non-caloric artificial sweetener. Overall, participants showed poor accuracy in discriminating drinks’ sweeteners, with significantly lower accuracy for SSBs than ASBs. Interestingly, we found a dissociation between sweetener recognition and drink pleasantness. In fact, in spite of a chance-level discrimination accuracy of SSBs, their taste was systematically preferred to the taste of non-caloric beverages. Our findings support the idea that hedonic value of carbonated soft drinks is dissociable from its identification and that the activation of the pleasure system seems not to require explicit recognition of the sweetener contained in the soft drink. We hypothesize that preference for carbonated soft drinks containing sugar over non-caloric alternatives might be modulated by metabolic factors that are independent from conscious and rational consumers’ choices.